Autonomes Fahren statt Stop and Go: Vorschläge zur effektiven Gestaltung der deutschen Kurzarbeit - Balleer, Almut; Gehrke, Britta; Hochmuth, Brigitte; Merkl, Christian (Perspektiven der Wirtschaftspolitik, 2019)
This article argues that short-time work stabilized employment in Germany substantially during the Great Recession in 2008/09. The labor market instrument acted in timely manner, as it was used in a rule-based fashion. In addition, discretionary extensions were effective due to their interaction with the business cycle. To ensure that short-time work will be effective in the future, this article proposes an automatic facilitation of the access to short-time work in severe recessions. This reduces the likelihood of a too extensive use at the wrong point in time as well as structural instead of cyclical interventions.
CRIS-Team Scopus Importer:2020-02-21